2016
DOI: 10.1002/mus.24972
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of muscle sizes in the lower limbs of children with cerebral palsy

Abstract: Heterogeneity across muscles and across subjects reinforces the subject specificity of CP and the need for individualized treatment planning. Muscle Nerve 53: 933-945, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 93 publications
(215 reference statements)
10
120
1
Order By: Relevance
“…This implies that the differing brain damage the children with CP have, has a greater impact on muscle growth than age and body size. This further supports the impression of great heterogeneity within CP previously reported (Handsfield et al, 2016) and underscores the need for structured, individualized longitudinal follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…This implies that the differing brain damage the children with CP have, has a greater impact on muscle growth than age and body size. This further supports the impression of great heterogeneity within CP previously reported (Handsfield et al, 2016) and underscores the need for structured, individualized longitudinal follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…cross-sectional growth of fibers) was attenuated. The substantial lower PCSA and the lower proximal and distal muscle volumes in children with SP is supported by previous studies reporting a lower ST muscle volume [26, 27, 29]. Note that the volume reduction in the current study (about 60%) exceeds that reported in previous studies (with about 35% volume reduction) [27, 29].…”
Section: Discussionsupporting
confidence: 87%
“…Given the relation between PCSA and force generation [69], the reduced PCSA observed in this study and the reduced muscle volume of ST (present study and [26, 27, 29]) suggest that, compared to TD children, in a majority of children with SP ST is weak. As lengthening of the ST tendon is presumed to induce even more ST weakness [16], a low preoperative PCSA of ST (i.e.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, in the triceps surae of children with SCP, there is a degree of homogeneity to the relative atrophy of these muscles. Compared with age‐matched controls, the MG, soleus (SOL), and lateral gastrocnemius (LG) were found to be 42%, 39%, and 36% smaller, respectively . The calculation of specific force is therefore presented with the knowledge that, at least in terms of muscle ACSA, there seems to be some degree of similarity in the relative differences between SCP and controls in the triceps surae.…”
Section: Methodsmentioning
confidence: 99%